2021
DOI: 10.3390/ijms222010913
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Binding Proteins for TSC22D1 Family Proteins Using Mass Spectrometry

Abstract: TSC-22 (TGF-β stimulated clone-22) has been reported to induce differentiation, growth inhibition, and apoptosis in various cells. TSC-22 is a member of a family in which many proteins are produced from four different family genes. TSC-22 (corresponding to TSC22D1-2) is composed of 144 amino acids translated from a short variant mRNA of the TSC22D1 gene. In this study, we attempted to determine the intracellular localizations of the TSC22D1 family proteins (TSC22D1-1, TSC-22 (TSC22D1-2), and TSC22(86) (TSC22D1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The TSC-22 domain family includes four members: TSC22D1/TSC-22, TSC22D2/KIAA0669, TSC22D3/GILZ, and TSC22D4/THG-1. The best-characterized member of this protein family is TSC22D1, which possesses a tumor-suppressor function, and TGF-β1-stimulated clone 22 (TSC-22/TSC22D1) was first identified as a target gene of TGF-β1 in mouse osteosarcoma cells [32,33]. In addition, our studies indicated a low frequency of TSC-22 SNP alleles in the population [34].…”
Section: Discussionmentioning
confidence: 61%
“…The TSC-22 domain family includes four members: TSC22D1/TSC-22, TSC22D2/KIAA0669, TSC22D3/GILZ, and TSC22D4/THG-1. The best-characterized member of this protein family is TSC22D1, which possesses a tumor-suppressor function, and TGF-β1-stimulated clone 22 (TSC-22/TSC22D1) was first identified as a target gene of TGF-β1 in mouse osteosarcoma cells [32,33]. In addition, our studies indicated a low frequency of TSC-22 SNP alleles in the population [34].…”
Section: Discussionmentioning
confidence: 61%
“…A previous study has attributed the effect of glucocorticoid on the activity of adenylate cyclase 50 . Specifically, the TSC22 protein family showed direct binding with this enzyme 51 . Moreover, the fact that TSC22D3 is in WGNCA|HepG2:235 annotated for ‘adenylate cyclase-inhibiting activity’ suggested the connection between activity of this enzyme with proliferation 52 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has attributed the effect of glucocorticoid on the activity of adenylate cyclase ( Aksoy et al , 2002 ). Specifically, the TSC22 protein family showed direct binding with this enzyme ( Kamimura et al , 2021 ). Moreover, the fact that TSC22D3 is in WGNCA|HepG2:235 annotated for “adenylate cyclase-inhibiting activity” suggested the connection between activity of this enzyme with proliferation.…”
Section: Discussionmentioning
confidence: 99%